Association between chronic bladder catheterisation and bladder cancer incidence and mortality: a population-based retrospective cohort study in Ontario, Canada - Ying Liu; Steven A Narod; Rano Matta; Ronald Kodama; Lesley Carr; Refik Saskin; Sender Herschorn; Robert K Nam; Amanda E Hird; Yuna Lee; Khaled Ajib; Girish S Kulkarni (BMJ Open)
Objectives To compare the risk of bladder cancer and bladder cancer mortality among patients with chronic bladder catheterisation (indwelling or intermittent) to patients from the general population.Design Retrospective cohort study.Setting Population-based study in Ontario, Canada between 2003 and 2018.Participants Adult patients 18–90 years of age with chronic bladder catheterisation were hard matched to patients from the general population without a history of bladder catheterisation.Interventions The presence of a chronic catheter was defined as a minimum of two physician encounters for bladder catheterisation, suprapubic tube insertion or home care for catheter care separated by at least 28 days. Urinary tract infection (UTI) rates were collected.Main outcome measures Bladder cancer and bladder cancer-specific mortality after a 1-year lag period were compared between groups.Results We identified 36 903 patients with chronic catheterisation matched to 110 709 patients without a history of catheterisation. Patients were followed for a median of 8.8 years (IQR: 5.2–11.9 years). The median age was 62 years (IQR: 50–71) and 52% were female. More patients in the catheter group developed bladder cancer (393 (1.1%) vs 304 (0.3%),p<0.001). There were 106 (0.3%) bladder cancer deaths in the catheter group and 59 (0.1%) in the comparison group (p<0.001). Chronic catheterisation (adjusted subdistribution HR (sdHR)=4.80, 95% CI: 4.26 to 5.42,p<0.001) and the number of UTIs (adjusted sdHR=1.04 per UTI, 95% CI: 1.04 to 1.05,p<0.001) were independent predictors of bladder cancer. The relative rate of bladder cancer-specific death was more than eightfold higher among patients with chronic catheterisation (adjusted sdHR=8.68, 95% CI: 6.97 to 10.81,p<0.001). Subgroup analysis among patients with neurogenic bladder and bladder calculi similarly revealed an increased risk of bladder cancer diagnosis and mortality. Bladder cancer risk was highest among patients in the two longest catheter duration quintiles (2.9–5.9 and 5.9–15.5 years).Conclusions This is the first study to quantify the increase in bladder cancer incidence and mortality in a large, diverse cohort of patients with chronic indwelling or intermittent bladder catheterisation. The risk was highest among patients with a chronic catheter beyond 2.9 years.